Essential Clinical Skills in Pediatrics A Practical Guide to History Taking and Clinical Examination - Qais Saadoon, Anwar (Springer International Publishing, 2018)
This book is a concise learning guide dedicated to the full scope of pediatric history-taking and clinical examination for use in OSCEs as well as clinical life. This book by Dr. Anwar Qais is a tour de force for the young doctor embarking on a career in Pediatrics. Full of detailed information on how to take a thorough clinical history and perform a detailed clinical examination. This book provides the explicit knowledge background required to take the early steps to become a competent children's doctor. I can strongly recommend this book as an essential read for all young aspiring Pediatricians. Hamish Wallace, MBBS, MD, FRCP, FRCPCH, FRCS, Professor of Pediatric Oncology, University of Edinburgh, Edinburgh, UK This practical and very informative introduction to the evaluation of a child will be invaluable in successfully learning the art of pediatrics. Tables and figures, along with salient highlights enhance the readability and usefulness. It is a gem. F. Bruder Stapleton, MD, Professor and Chair, Department of Pediatrics, University of Washington School of Medicine, Washington, USA Essential Clinical Skills in Pediatrics is written as a very practical guide for healthcare providers who are looking for a comprehensive roadmap to a thorough history and complete physical examination in children. The use of lists and tables makes it visually easy to follow and very user-friendly. The author has also sprinkled in some helpful clinical tips and highlighted some useful key learning points. Dr. Qais should be congratulated for a job well done. Jeremy Friedman, MBChB, FRCP, Professor of Pediatrics, University of Toronto, Toronto, Canada The book Essential Clinical Skills in Pediatrics has been a tremendous effort by the author. It is written in a simple and concise manner, with the clarity needed to quickly pick up important points. It is quite complete and incorporates the main findings that pediatric residents and specialists need to know during a history and physical. The lecture-note style, using short sentences and lists of important features, is particularly appreciated. I think that this book will be helpful for a wide audience of physicians, not only those specialists in pediatrics but also general practitioners who may see children in their practice. Rolando Cimaz, MD, Associate Professor of Pediatrics, University of Florence, Florence, Ital.